2023
DOI: 10.3390/en16062793
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of Cost-Effective Electrification of Long-Distance Line-Haul Trucks

Abstract: This paper investigates the economic consequences of a haulage company replacing its line-haul diesel trucks with battery-electric ones. It also examines how large truck batteries should be, whether the haulage companies should use public fast chargers to complement their own, and whether public fast chargers have the potential to be profitable. The potential extra cost of losing payload capacity is estimated and there is an investigation of whether a charge-point operator should meet the peak demand for charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Several research studies show BETs' feasibility [13][14][15][16] and economic competitiveness [17][18][19] compared to today's diesel trucks. Previous work in the BET context deals with the topics of battery dimensioning [17,20,21] and cell selection [18,20,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research studies show BETs' feasibility [13][14][15][16] and economic competitiveness [17][18][19] compared to today's diesel trucks. Previous work in the BET context deals with the topics of battery dimensioning [17,20,21] and cell selection [18,20,22].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [14,17,19,20] investigate the influence of these intermediate fast-charging events with different charging powers on the battery dimensioning, cell selection, and TCO. For this purpose, either synthetic scenarios [14,17,20] based on the hour of service (HoS) regulations applicable in the EU [23] or an explicit route with defined stops for the charging events are used [19]. Only a few studies investigate the required charging infrastructure for BET.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the oil depletion time is less than 30 years [1], the Earth's climate system has likely been affected [2], and several adverse health impacts have emerged, as expressed in the literature [3]. Battery electric trucks seem to be a part of the solution since several studies have concluded that battery electric trucks could become a cost-efficient, fossil-free alternative to today's commercial diesel trucks [4][5][6][7][8]. The literature shows that the cost-effectiveness of battery electric trucks is sensitive to driving patterns [4], whereas relatively uniform driving patterns are most suitable for electrification [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…The literature also highlights other essential factors for cost-effective battery electric vehicles, such as the battery price [15,16] and size [4,17]. Further, the price of public fast charging could strongly impact the cost-effectiveness, battery sizing and charging strategy [5]. Charger utilisation must be high enough for the installation of chargers to be worthwhile [18], and high utilisation is also a prerequisite for cheap public fast charging [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation